Helicobacter pylori and its role in the pathogenesis of follicular gastritis: an overview - Carlosama-Rosero, Yeison (2024)
The role of Helicobacter pylori in the pathogenesis of peptic ulcers and gastric adenocarcinoma is widely known; however, it is not entirely understood how bacterial infection is closely related to the genesis of follicular gastritis and some types of gastric lymphoma. Diagnosing and pathogenic mechanisms follicular gastritis remain challenging. Therefore, this article aims to examine the role of H. pylori in the development of follicular gastritis. In addition, it emphasizes the clinical and histopathological fundamentals. A broader overview of follicular gastritis is presented, and implementing preventive strategies, such as H. pylori eradication remains the standard treatment.